Lenalidomide versus bortezomib maintenance after frontline autologous stem cell transplantation for multiple myeloma - Bärtsch, Marc-Andrea; Mai, Elias K.; Hielscher, Thomas; Bertsch, Uta; Salwender, Hans J.; Munder, Markus; Fuhrmann, Stephan; Dührsen, Ulrich; Brossart, Peter; Neben, Kai; Schlenzka, Jana; Kunz, Christina; et al. (Blood cancer journal, 2021)
Lenalidomide (LEN) maintenance (MT) post autologous stem cell transplantation (ASCT) is standard of care in newly diagnosed multiple myeloma (MM) but has not been compared to other agents in clinical trials. We retrospectively compared bortezomib (BTZ; n = 138) or LEN (n = 183) MT from two subsequent GMMG phase III trials. All patients received three cycles of BTZ-based triplet induction and post-ASCT MT. BTZ MT (1.3 mg/m2 i.v.) was administered every 2 weeks for 2 years. LEN MT included two consolidation cycles (25 mg p.o., days 1-21 of 28 day cycles) followed by 10-15 mg/day for 2 years. The BTZ cohort more frequently received tandem ASCT (91% vs. 33%) due to different tandem ASCT strategies. In the LEN and BTZ cohort, 43% and 46% of patients completed 2 years of MT as intended (p = 0.57). Progression-free survival (PFS; HR = 0.83, p = 0.18) and overall survival (OS; HR = 0.70, p = 0.15) did not differ significantly with LEN vs. BTZ MT. Patients with <nCR after first ASCT were assigned tandem ASCT in both trials. In patients with <nCR and tandem ASCT (LEN: n = 54 vs. BTZ: n = 84), LEN MT significantly improved PFS (HR = 0.61, p = 0.04) but not OS (HR = 0.46, p = 0.09). In conclusion, the significant PFS benefit after eliminating the impact of different tandem ASCT rates supports the current standard of LEN MT after ASCT.
Gesehen am 10.03.2021